Effects of feeding ratio on growth and food conversion rate of common carp Cyprinus carpio reared in floating cages - Taher, Majid Makky; Al-Dubakel, Adel Yacob; saleh, Jassim Hameed (Iraqi Journal of Aquaculture, 2022)
Effects of feeding ratios (3%, 5% and 7%) on growth and food conversion rate (FCR) of common carp Cyprinus carpio reared in floating cages at Shatt Al-Arab River, Hartha district were studied during a period of 27-4-2010 to 28-6-2010. Statically analysis of results proved that there were significant differences between final weight and length reached by fishes fed on 3% of fish weight and fished fed on 5% and 7% of fish weight. Final weights of fishes were (188, 275.8 and 252.6) g and final lengths were (216.6, 234.6 and 227.2) mm for (3, 5 and 7)% feeding ratio respectively. Better results of growth and FCR obtained from fishes fed 5% of fish weight. Results appeared that FCR values were 4.82, 2.63 and 3.98, daily growth rates were (1.07, 3.16 and 2.78) g/day and specific growth rates were (0.7, 1.85 and 1.71) %/day for fishes fed 3, 5 and 7% of fish weight respectively.